(untitled) - Goldman, Thomas F. (Upper Saddle River, N.J., 2002)
On-the-job Paralegals, Legal Assistants, and Legal Secretaries desire accounting materials that apply to their job responsibilities.
Keywords: Lawyers,Lawyers,Luật sư,Luật sư; Accounting,Taxation,Kế toán,Hệ thống thuế; United States,Hoa Kỳ